2018
DOI: 10.1016/j.mcp.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Duplex real-time polymerase chain reaction assay for the detection of human KIPyV and WUPyV in nasopharyngeal aspirate pediatric samples

Abstract: In this study, we describe a duplex real-time PCR assay for the simultaneous detection of KIPyV and WUPyV polyomaviruses based on TaqMan probes. This assay detected 500 copies/mL both for KIPyV and WUPyV in 100% of tested positive samples. We assessed this technique on 482 nasopharyngeal aspirate specimens from hospitalized pediatric patients with respiratory symptoms, previously analyzed with commercial multiplex assay for 16 major respiratory viruses. Our assay detected KIPyV genome in 15 out of 482 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Ligozzia, et al . in Italy reported that of 482 patients aged younger than 5, KIPyV (3.1%) and WUPyV (4.9%) were detected (14). In one study in China, 406 nasopharyngeal aspirate samples were collected from children with acute respiratory symptoms by Yuan et al The mean age of the patients was about 2 years old, 60% were male and 40% were female.…”
Section: Discussionmentioning
confidence: 99%
“…Ligozzia, et al . in Italy reported that of 482 patients aged younger than 5, KIPyV (3.1%) and WUPyV (4.9%) were detected (14). In one study in China, 406 nasopharyngeal aspirate samples were collected from children with acute respiratory symptoms by Yuan et al The mean age of the patients was about 2 years old, 60% were male and 40% were female.…”
Section: Discussionmentioning
confidence: 99%